A comparative study of Vietnamese and international accounting standards - Pham, Hoai Huong (Curtin University, 2012)
This thesis investigates de jure convergence of Vietnamese Accounting Standards (VAS) and International Accounting Standards (IAS/IFRS) and de facto (actual company reporting practice) compliance with VAS and IAS/IFRS using a sample of 200 Vietnamese listed companies’ 2010 annual financial reports. This study is important because Vietnam is one of Asia’s fastest growing economies whilst Vietnamese accounting is poorly understood.The de jure analysis shows that during the period 2001-2005 Vietnam initially adopted 84% of the IAS/IFRS issued up through 2003. However, subsequent amendments and new IFRSs have not been updated to VASs, causing a significant decrease in overall de jure convergence to a very modest level of 62%. Non-convergence is more noticeable for disclosure than for measurement issues.The de facto analysis shows a somewhat higher level (80%) of compliance with VAS but a lower level (67%) of compliance with IAS/IFRS by Vietnamese listed companies. Disclosure non-compliance is particularly problematic for Vietnam. State ownership, company size and audit firm type are major predictors of measurement compliance, whereas stock exchange location and audit firm type are key predictors of disclosure compliance.The modest de jure convergence of VAS and IAS/IFRS combined with the moderate de facto company compliance with VAS leads to a lower de facto compliance with IAS/IFRS in Vietnam. The key implication is that enhancement of mechanisms for complying with accounting standards is as important as improvement of de jure convergence to achieve de facto company reporting convergence with IAS/IFRS in Vietnam. This highlights the role of national accounting standard setters and regulators in promoting the convergence process. From a more global perspective, if the International Accounting Standards Board is to truly achieve its global convergence aim they should review their rule-making approach for emerging markets like Vietnam.